2011
DOI: 10.1128/jcm.00935-11
|View full text |Cite|
|
Sign up to set email alerts
|

Aortic Homograft Endocarditis Caused by Campylobacter jejuni

Abstract: We report the first case of homograft endocarditis caused by Campylobacter jejuni, which was treated successfully with antibiotic therapy and valve replacement. To our knowledge, only two other cases of C. jejuni endocarditis, involving native valves, have been reported in the medical literature. CASE REPORTIn May 2009, a 46-year-old male born in Morocco and living in The Netherlands for the past 22 years was admitted to the hospital with a 3-month history of recurrent fever and general weakness. The patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Campylobacter-associated endocarditis is an infrequent condition in which both native and prosthetic valves can be affected. Previous studies have shown that individuals with Campylobacterassociated endocarditis have either C. jejuni or C. fetus infection and that one-third of these patients suffer from concurrent chronic diseases, including hepatic cirrhosis, connective tissue disease, tuberculosis, or cancer (233)(234)(235)(236)(237)(238)(239). Furthermore, four cases of atrial fibrillation associated with C. jejuni infection have been reported in the literature (230,240), and both C. jejuni and C. fetus infections have been associated with Campylobacter-associated aortitis (241)(242)(243)(244).…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Campylobacter-associated endocarditis is an infrequent condition in which both native and prosthetic valves can be affected. Previous studies have shown that individuals with Campylobacterassociated endocarditis have either C. jejuni or C. fetus infection and that one-third of these patients suffer from concurrent chronic diseases, including hepatic cirrhosis, connective tissue disease, tuberculosis, or cancer (233)(234)(235)(236)(237)(238)(239). Furthermore, four cases of atrial fibrillation associated with C. jejuni infection have been reported in the literature (230,240), and both C. jejuni and C. fetus infections have been associated with Campylobacter-associated aortitis (241)(242)(243)(244).…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Consistent with an enteropathogen-induced dispersion of pathobionts, the transient infection promoted the translocation of commensal bacteria to the spleen and liver, depolarized epithelial TLR9, and worsened post-infectious DSS colitis [65]. These observations shed light on how infections with C. jejuni , and other enteropathogens, including parasites and viruses, may exacerbate inflammation in patients with IBD, lead to post-infectious Irritable Bowel Syndrome, and perhaps contribute to extra-intestinal complications, such as haemolytic-uremic syndrome, endocarditis, and a variety of others [52, 6671]. Recent studies found that human microbiota rendered dysbiotic by exposure to enteropathogens, of when obtained from patients with IBD, in association with their elevated content of activated virulence genes, cause lethal toxicity in the nematode Caenorhabditis elegans [26, 72].…”
Section: Introductionmentioning
confidence: 99%
“…Such complications have also been reported in patients hospitalized with Campylobacter-related bacteremia and underlying health problems such as Campylobacterrelated meningitis [80,81], hepatitis [82], arthritis [83], abdominal septic aortic pseudoaneurysm [84], peritonitis [85,86], acute pancreatitis [87,88], cellulitis [89,90], pericarditis [91], endocarditis [92] and hemolytic uremic syndrome (HUS) [93]. Again, these reports indicate that Campylobacter is able to efficiently travel through the blood stream in gastroenteritis patients, specifically to tissues or organs that can only be reached via the circulating blood stream.…”
Section: Timing Of Detection In Hospitalsmentioning
confidence: 90%